THE DESIGN OF TERM LIMITATIONS FOR THE REPUBLIC OF INDONESIA'S HOUSE OF REPRESENTATIVES MEMBERS: CONSTITUTIONAL ANALYSIS, REPRESENTATIVE DEMOCRACY, AND THE CHECKS AND BALANCES MECHANISM - Sulistafando, Ravidan Maheer; Elviandri; Yulianingrum, Aullia Vivi; Hasmiati, Rahmatullah Ayu (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The absence of term limits for legislative members has resulted in a pattern of power entrenchment, thus hampering the process of leadership regeneration and strengthening oligarchic tendencies within parliament. The absence of term limits in the Law of MD3 opens up space for power entrenchment, the formation of political dynasties, conflicts of interest, and a decline in the integrity of representation, reflected in the increasing constituency disconnect, the phenomenon of self-serving legislation, and the high number of legislative corruption cases. Therefore, a comprehensive design is needed to formulate a term limit model that aligns with the constitutional mandate. The study uses normative legal methods through legislative and conceptual approaches, examining the 1945 Constitution, the MD3 Law, the Election Law, Constitutional Court decisions, as well as the theories of constitutionalism, Habermas's deliberative democracy, and Madison's theory of power limitations. The analysis is conducted descriptively-analytical and interpretative-normative to build a cohesive legal argument. The results show that constitutionally, term limits can be justified as an integral part of the principle of power limitation and legal certainty; the current absence of norms has been shown to reduce the effectiveness of the representation function and open up opportunities for abuse of authority. From a leadership regeneration perspective, term limits increase the plurality of political actors, reduce incumbency advantage, and encourage policy innovation, while simultaneously breaking patronage networks that hamper oversight functions. Meanwhile, from a checks and balances perspective, term limits can strengthen the collegial independence of the House of Representatives (DPR) and increase the credibility of its oversight function over the executive, but they need to be designed proportionally to avoid creating an expertise gap or disrupting policy continuity.